Uma proposta de ensino de efeito Doppler a partir de uma técnica de detecção de exoplanetas - Costa, Rayrison Tobias (2021)
The purpose of this work is to evaluate a Potentially Meaningful Teaching Unit (PMTU) that makes use of the theme exoplanets for teaching the Doppler effect. Every PMTU implementation is guided by David Ausubel's Theory of Meaningful Learning. The intervention was carried out entirely on virtual platforms and all 37 participating students are regularly enrolled in the second year of high school of Instituto Federal de Educação, Ciência e Tecnologia do Mato Grosso (IFMT) – campus Cáceres. The teaching unit was applied over five weeks, each one corresponding to a different stage. The verification of the results was carried out by examining the productions of the participating students and the teacher's records. The investigation is focused on two aspects: 1) look for evidence of meaningful learning; 2) point out evidences of the processes of progressive differentiation and integrative reconciliation. The analysis of the students' productions and clippings of their participation showed that the conditions for meaningful learning were met, mainly seen by the high approval rate of the learning material. Furthermore, the concept maps revealed satisfactory indications of progressive differentiation and integrative reconciliation.